Probiotic supplementation in diets for laying hens and its effects on the internal quality of eggs stored under refrigeration - Larissa Faria Silveira Moreira; Rosiane de Souza Camargos; Alexander Alexandre de Almeida; Carla Pantano; Rogério Amaro Gonçalves; Adriano Geraldo (Acta Scientiarum. Animal Sciences, 2025)
This study aimed to evaluate probiotics supplementation in diets for semi-heavy layers hens and their effects on the internal quality of eggs stored under refrigeration for different periods. 210 Hisex Brown® laying hens aged 30 weeks were  distributed in a completely randomized design wIth six treatments, and seven replications,. The experimental diets were offered for 112 days. The experimental diets were: Control: control diet, without the inclusion of probiotics and feed efficiency-enhancing additives; CP: positive control feed with the inclusion of a feed efficiency-enhancing additive (Halquinol antibiotic inclusion at 60g kg-1); C+100: control feed with the inclusion of 100 g t-1 of a product based on Bacillus subtilis (Bacillus subtilis guaranteed level 2.0*106 CFU/g); C+150: feed with the inclusion of 150 g t-1 of the Bacillus subtilis-based product; C+200: feed with the inclusion of 200 g t-1 of Bacillus subtilis-based product; C+250: feed with the inclusion of 250 g t-1 of Bacillus subtilis-based product. A total of 588 eggs collected in the experimental plots were used (2 eggs per plot), and storage times at room temperature were 0, 5, 10, 15, 20, 25, and 30 days and were analyzed for internal egg quality. Probiotic supplementation did not influence the internal quality of the eggs. The storage time under refrigeration influenced the percentage and quality of the eggs' internal components and weight loss, with worse results in eggs stored for longer.